OPTIMALISASI PROSES DAN PERAN FORKOM PTNU (PRESPEKTIF MANAJEMEN DAN PENGEMBANGAN MASYARAKAT BANYUWANGI) - Rahman, Kholilur (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2021)
On Friday, February 25, 2021 PC NU Banyuwangi held a discussion event NU academics by inviting Rector of IAI Ibrahimy Genteng, Rector of IAI Darussalam Blokagung Karangdoro and Chairman of STAI Darul Ulum Sumberberas. The discussion decided the establishment of PTNU Banyuwangi Communication Forum as a forum for friendship of NU academics. This forum places the top level of management in its structure. Kh. Ahmad Munib Syafa'at, L.c., M.EI. (Rector of IAIDA) was appointed as the leader of the forum. This forum sets out the vision of "consolidated NU academics for the benefit of jam'iyah and NU Banyuwangi citizens, with the mission of becoming a reference forum for every issue both internal NU and external NU. The forum also sets out the working program: (a) regular thematic discussions (switching campuses) every month; (b) the lecturers are assisted to accompany institutions and banom and structures under PCNU, especially madrasahs under LP Ma'arif; (c) collaborative research on themes related to the existence of NU. Given the new age of this forum, its existence needs to be optimized, although some campuses have partially performed their role in community development, both individually and institutionally. This article (a) will review the optimalisasai process of PTNU in Banyuwangi, especially those incorporated in the PTNU Banyuwangi Communication Forum; (b) the prospect of its role for community development in the management perspective.